2020
DOI: 10.3389/fneur.2020.00247
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Decline and Related Cognitive Deficits

Abstract: Since late stage dementia, including Alzheimer's disease (AD), cannot be reversed by any available drugs, there is increasing research interest in the preclinical stage of AD, i.e., subjective cognitive decline (SCD). SCD is characterized by self-perceptive cognitive decline but is difficult to detect using objective tests. At SCD stage, the cognitive deficits can be more easily reversed compared to that of mild cognitive impairment (MCI) and AD only if accurate diagnosis of SCD and early intervention can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 110 publications
(69 reference statements)
0
37
0
2
Order By: Relevance
“…However, it is important to note that both brain activity and FC significantly decreased as early as in SCD. This suggests that dysregulation of brain neuronal excitability appears before objective impairment upon formal testing and that might be a potential biomarker (Mattson and Arumugam, 2018 ; Si et al, 2020 ). Interestingly, the FC strength between LPCUN and the altered regions of the brain in the AD group showed an increasing trend compared to the SCD and MCI groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that both brain activity and FC significantly decreased as early as in SCD. This suggests that dysregulation of brain neuronal excitability appears before objective impairment upon formal testing and that might be a potential biomarker (Mattson and Arumugam, 2018 ; Si et al, 2020 ). Interestingly, the FC strength between LPCUN and the altered regions of the brain in the AD group showed an increasing trend compared to the SCD and MCI groups.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that the prevalence of SCD ranges from 10 to 88% and increases with age: 20% in people 65 years and younger, 25-50% in people 65 years and older, and 88% in people over 85 years of age (Gifford et al, 2015). For SCD, memory decline is the most common symptom, and at the same time it can be accompanied by visual-spatial impairment, language impairment, attention deficit, and other symptoms (Si et al, 2020). According to statistics, an estimated 27% of SCD patients will develop MCI in the future, and another 14% will eventually be diagnosed with cognitive impairment (Mitchell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Third, our subjective cognitive complaint questionnaire has not been validated. In fact, validated tools for evaluating subjective cognitive decline are still under development 66 . We attempted to use a comprehensive questionnaire as an exploratory tool to measure subjective cognitive complaints, correlations to the cognitive problems of SSS, and objective cognitive performance (Supplementary Tables S4 and S5 ) in our study, which may support the validity of our subjective cognitive complaint questionnaire.…”
Section: Discussionmentioning
confidence: 99%